Episiotomy or perineal tears: compared with catgut, synthetic sutures reduce risk of short-term pain and need for resuturing; rapidly absorbing sutures comparable to synthetic but reduce the need for suture removal. Issue 1 (24th September 2010) - Fernando, Ruwan
Abstract : Commentary on: Kettle C Dowswell T Ismail KM . Absorbable suture materials for primary repair of episiotomy and second degree tears . Cochrane Database Syst Rev 2010 ;6 :CD000006 .